Nanotechnology-based delivery of CRISPR/Cas9 for cancer treatment - Xu, Xiaoyu; Liu, Chang; Wang, Yonghui; Koivisto, Oliver; Zhou, Junnian; Shu, Yilai; Zhang, Hongbo (Advanced drug delivery reviews, 2021)
[Display omitted] CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats-associated protein 9) is a potent technology for gene-editing. Owing to its high specificity and efficiency, CRISPR/Cas9 is extensity used for human diseases treatment, especially for cancer, which involves multiple genetic alterations. Different concepts of cancer treatment by CRISPR/Cas9 are established. However, significant challenges remain for its clinical applications. The greatest challenge for CRISPR/Cas9 therapy is how to safely and efficiently deliver it to target sites in vivo. Nanotechnology has greatly contributed to cancer drug delivery. Here, we present the action mechanisms of CRISPR/Cas9, its application in cancer therapy and especially focus on the nanotechnology-based delivery of CRISPR/Cas9 for cancer gene editing and immunotherapy to pave the way for its clinical translation. We detail the difficult barriers for CRISIR/Cas9 delivery in vivo and discuss the relative solutions for encapsulation, target delivery, controlled release, cellular internalization, and endosomal escape.